Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn206
|View full text |Cite
|
Sign up to set email alerts
|

Attention

Abstract: Attention refers to the set of ever‐present functions that prioritize and select information to guide adaptive behavior. As such, it is fundamental to almost all aspects of cognition. In this chapter, we review the psychological and neuroscientific literatures concerned with understanding its principles and mechanisms. We chart the scientific advances that have brought us to the appreciation that all levels of information processing are continuously, proactively, and dynamically modulated according to our goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 479 publications
0
7
0
Order By: Relevance
“…These two phenomena nicely illustrate the flexibility with which memory-related traces can be used to guide adaptive performance. The specific consequence of prior knowledge will be heavily dependent on the purpose of the task (Nobre, 2018). “Episodic future thinking” involves drawing on previous experiences to imagine oneself in future situations (Atance and O’Neill, 2001, Schacter et al., 2008).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…These two phenomena nicely illustrate the flexibility with which memory-related traces can be used to guide adaptive performance. The specific consequence of prior knowledge will be heavily dependent on the purpose of the task (Nobre, 2018). “Episodic future thinking” involves drawing on previous experiences to imagine oneself in future situations (Atance and O’Neill, 2001, Schacter et al., 2008).…”
Section: Main Textmentioning
confidence: 99%
“…These two phenomena nicely illustrate the flexibility with which memory-related traces can be used to guide adaptive performance. The specific consequence of prior knowledge will be heavily dependent on the purpose of the task (Nobre, 2018).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using word stimuli further showed that modulation could include lexical and semantic content (McCarthy and Nobre, 1993; Bentin et al, 1995), challenging views about the automatic nature of such stages of processing (Deutsch and Deutsch, 1963). ERP studies also clearly showed early sensory modulatory effects of object-based (Valdes-Sosa et al, 1998), feature-based (Hansen and Hillyard, 1983; Leonards et al, 2003; Hopf et al, 2004), and temporal (Doherty et al, 2005) attention, thus helping the field break away from the notion of a privileged type of unit for attention selection (see Nobre and Silvert, 2008; Nobre and Kastner, 2014; Nobre, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As we explore our cluttered world throughout childhood and adulthood, multiple sources influence where we orient our attention. Salient external events engage orienting mechanisms (e.g., Nobre, 2018;Posner, 1980;Posner & Peterson, 1990), facilitating our ability to detect or discriminate novel objects in our environments (Henderson, 1991;M€ uller & Rabbitt, 1989). Past experiences and their associated spatial memories also orient attention to relevant information (e.g., Giesbrecht, Sy, & Guerin, 2013;Goldfarb, Chun, & Phelps, 2016;Merrill, Conners, Roskos, Klinger, & Klinger, 2013;Rosen, Stern, & Somers, 2014;Rosenbaum & Jiang, 2013;Summerfield, Lepsien, Gitelman, Mesulam, & Nobre, 2006).…”
mentioning
confidence: 99%